Rosacea. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 1. Epidemiology, classification and clinical presentation - Anna Woźniacka; Joanna Czuwara; Dorota Krasowska; Ewa Chlebus; Grażyna Wąsik; Anna Wojas-Pelc; Lidia Rudnicka; Joanna Narbutt; Zygmunt Adamski; Aleksandra Batycka-Baran; Rafal Czajkowski; Magdalena Czarnecka-Operacz; et al. (Termedia Publishing House, 2022)
Rosacea is a chronic, relapsing, inflammatory, but not infectious, skin disease. The prevalence of rosacea is relatively high in the adult population of Northern Europe. Its characteristic symptoms include recurrent flushing, erythema, telangiectasia, papules and pustules, localized on cheeks, nose, chin and forehead. At present, four, not mutually exclusive subtypes of acne are classified: erythematotelangiectatic, maculopapular, hypertrophic and ocular. The clinical presentation of this dermatosis is heterogeneous. Clinical symptoms and their severity may vary individually. For this reason, treatment should be individualized and take into consideration the type of cutaneous lesions, presence of comorbidities, patient's occupation, impact of the disease on the quality of life, and patient's preferences. In addition to topical and systemic medications, adequate skin care is important.